Pneumatic jigging: influence of operating parameters on separation efficiency of solid waste materials - Mohd Aizudin, Abd Aziz; Khairuddin, Md Isa; Radzuwan, Ab Rashid (SAGE Publications Ltd, 2017)
This article aims to provide insights into the factors that contribute to the separation efficiency of solid particles. In this study, a pneumatic jigging technique was used to assess the separation of solid waste materials that consisted of copper, glass and rubber insulator. Several initial experiments were carried out to evaluate the strengths and limitations of the technique. It is found that despite some limitations of the technique, all the samples prepared for the experiments were successfully separated. The follow-up experiments were then carried out to further assess the separation of copper wire and rubber insulator. The effects of air flow and pulse rates on the separation process were examined. The data for these follow-up experiments were analysed using a sink float analysis technique. The analysis shows that the air flow rate was very important in determining the separation efficiency. However, the separation efficiency may be influenced by the type of materials used.